Influence of Embedded Material on Natural Frequencies of Double Segment Rotating Disk - Sarfaraz, Ehsan; Hamidzadeh, Hamid R. (Journal of Applied Nonlinear Dynamics, 2026)
An analytical method is presented to determine the effect of adding different materials at one of the edges of an annular rotating disk on its in-plane natural frequencies and critical speeds. The proposed analysis is based on the linear in-plane free vibration of a compound disk with material discontinuity, by adopting the two-dimensional plane stress theory. The frequency equation was achieved by satisfying the compatibilities of the displacements and stresses at the interfaces of the different segments. The materials used in each segments of the disk are assumed to be homogenous,elastic, and isotropic. Furthermore, the annular disk is considered to be clamped at the inner side and free at the outer edge with a radius ratio of 0.3, and rotates with a constant angular speed. The variation of non-dimensional natural frequencies in fixed coordinates for different modes and different segment radiuses at the inner or outer side with respect to speed of rotation are computed. Presented results indicated that by adding additional segment, undesirable natural frequencies of the rotating disk can be modified to be within the acceptable range.